Kekuatan Hukum Sertifikat Hak Tanggungan yang Terbit atas Adanya Unsur Onbeschikking Bevoeg Pemberi Hak Tanggungan atas Obyek Hak Tanggungan - Felix Rovi Lindartanto; Dewi Astutty Mochtar; Diah Aju Wisnuwardhani (Postgraduate University of Merdeka Malang, 2025)
The lack of authority of a party who does not have the right to place a mortgage on a creditor which in the future results in a dispute, whether criminal or civil, has different legal consequences. So it is appropriate to know the legal strength of proof of the mortgage right certificate in terms of the registration system in Indonesia and the legal consequences of issuing mortgage rights which occur on the basis of the mortgagor's lack of authority over the object of the mortgage right. The research uses normative research methods with analytical descriptive analysis techniques. The Mortgage Rights Certificate has strong evidentiary power if it meets three main aspects. First, the existence of cadastral data plots, namely data related to land conditions, such as location, area and land boundaries, which are obtained from accurate measurements of land plots. Second, creating a public register that records the names of land rights holders. This general list is officially managed by the relevant agencies and is a trusted source of information. Third, implementing a publication system that shows openness of information to the public, allows other parties to know the status of land rights clearly. In the context of the issuance of an invalid mortgage right due to non-compliance with applicable legal provisions, a mortgage right can be deemed to have no legal force if the party providing the mortgage right is not registered as the legal owner of the object in question. This will cause losses for the party who receives the mortgage right because they cannot rely on the mortgage right to execute the debt if the debtor does not fulfill his obligations. Non-compliance or violation of the authority and provisions governing legal validity can result in serious legal consequences, such as cancellation of mortgage rights, loss of rights to objects guaranteed, or even material losses for interested parties.